Principal's Strategy in Building an Inclusive Culture of SDN Mejing 2 Candimulyo District - Kusumaningrum, Fibria; Saryanto, Saryanto; Rejokirono, Rejokirono (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study aims to find out how strategies are used by school principals in building an inclusive school culture and the challenges and obstacles faced by school principals in building an inclusive culture. The research method used is a qualitative research method with an approach with interview, observation, and documentation techniques. Based on the results of the study, it can be concluded that the success of the principal of SDN Mejing 2 in building an inclusive school culture is the result of the implementation of a directed and comprehensive strategy and even though SDN Mejing 2 faces various challenges, both from within the school environment (internal) such as the teacher's lack of understanding of the concept of inclusion, limited facilities, and from outside (external) such as lack of parental support and community stigma, the principal did not stay silent. This evaluation process includes an assessment of the effectiveness of planning, program implementation, and the involvement of all school elements in realizing inclusive values